Hospitality internships in Cyprus: a genuine academic experience or a continuing frustration? - Zopiatis, Anastasios (My University, 2007)
Abstract: Purpose – The primary purpose of the research study conducted was to investigate hospitality internships and improve such practices within the distinct environment of the hospitality industry of Cyprus by acquiring new knowledge, related to and of value to its primary stakeholders. Design/methodology/approach – The unique characteristics of the three groups under investigation necessitated the utilization of different research methods and techniques – an approach known as methodological triangulation. Findings – While the findings reliably measure the Cyprus-specific environment, the author argues that the particular strategies produced can effectively be implemented in other countries. Practical implications – By comparing and contrasting the views and expectations of all stakeholders involved, the author recommends specific strategies for improving the quality and enhancing the value of internship practices for hospitality students. Originality/value – The paper is of value to all hospitality stakeholders, since it can serve as a guide for the provision of a pedagogically sound internship experience to students.
Keywords: Cyprus; Hospitality education; Hospitality management; Personality